[(2-Chlorophenyl)-(4-fluorophenyl)methylene]-(4-fluorophenyl)amine - Salvador Vilchis-Valdés; Alberto Cedillo-Cruz; Marco A. García-Eleno; Diego Martínez-Otero; Erick Cuevas-Yañez (Molbank)
The formation of a N,1,1-triaryl imine derived from (2-chlorophenyl)-bis-(4-fluorophenyl)methanol is reported. The title compound is formed from a consecutive process which involves a nucleophilic substitution and subsequent Schmidt reaction. A description of the synthesized compound’s NMR spectra is presented and the structure was unambiguously established by X-ray analysis. A Hirshfeld surface analysis is also included, confirming the presence of intermolecular H···F interactions involved in crystal packing.